Processes of policy borrowing in education: some explanatory and analytical devices - Phillips, D; Ochs, K (2003)
This paper addresses questions of policy 'borrowing' in education. Building on the authors' previous work, it proposes some explanatory and analytical devices to assist in the exploration of the processes involved in 'cross-national attraction' in educational policy and its consequences in terms of decision making, implementation, and 'internalisation'.